Efficacy and tolerability of injectable collagen-containing products in comparison to trimecaine in patients with acute lumbar spine pain (Study FUTURE-MD-Back Pain) - Pavelka, Karel; Jarošová, Hana; Milani, L; Procházka, Zdeněk; Kostiuk, Pavel; Kotlářová, Lucie; Meroni, Alberto Marco; Slíva, Jiří (Physiological research, 2019)
Low back pain (LBP) represents an important subgroup of vertebrogenic pain with estimated prevalence around 80 %. Locally acting injectable collagen for topical application has recently extended the limited range of treatment options. The aim of the study was to evaluate the efficacy and safety of injectable collagen in patients with LBP. Patients suffering from LBP (< three months) were enrolled. They were administered either collagen 4 ml or trimecaine 1 % 4 ml in the form of subcutaneous paravertebral injections into eight pre-specified points (0.5 ml per each point) in the following schedule: two administrations in the first and second week, one in the third week. The pain intensity, Thomayer distance, Oswestry disability index, Lasseque test, quality of life, consumption of rescue medication and safety were evaluated. Exertional and rest pain, evaluated by a visual analogue scale, gradually decreased in both groups. Both treatments showed a statistically significant improvement in mobility and quality of life. The consumption of paracetamol as a rescue medication was significantly lower in patients treated with collagen than in the group treated with trimecaine (p=0.048). The analgesic efficacy of locally acting injectable collagen, as well as an analgesic sparing effect when compared to local anesthetics were demonstrated.
Keywords: dospělí; trimekain; Female; jednoduchá slepá metoda; Adult; Analgesics; výsledek terapie; ženské pohlaví; rostlinné extrakty; Collagen; lidé; kolagen; Low Back Pain; Treatment Outcome; Acute Pain; Trimecaine; Hamamelis; Single-Blind Method; akutní bolest; prospektivní studie; Male; Plant Roots; Aged; Prospective Studies; lumbalgie; analgetika; Plant Extracts; lidé středního věku; senioři; mužské pohlaví; kořeny rostlin; Middle Aged; Humans